Destruction of biofilms under the influence of Acinetobacter calcoaceticus IMV B-7241 surfactants, synthesized in the presence of competitive microorganisms - Pirog, Tatiana; Ivanov, Mykyta (My University, 2022)
Introduction. The aim of this study was to investigate the role of surfactants synthesized by Acinetobacter calcoaceticus IMV B-7241 in media with glycerol in the presence of biological inductors in destruction of biofilms. Materials and methods. Cultivation of A. calcoaceticus IMV B-7241 was carried out in a mineral medium using refined glycerol or crude glycerol, the waste of biodiesel production, as carbon sources. Biological inductors were introduced as live or inactivated cells of Bacillus subtilis BT-2, as well as the supernatant after strain BT-2 cultivation. Surfactants were extracted from the supernatant of the culture liquid with a modified mixture of Folch (chloroform and methanol, 2:1). The degree of biofilm destruction in the presence of surfactants was determined by spectrophotometric method. Results and discussion. Regardless of the substrate used, the introduction of both live and inactivated cells of B. subtilis BT-2 into medium used for cultivation of A. calcoaceticus IMV B-7241 was accompanied by the synthesis of surfactants, the degree of biofilm destruction of which was higher than those obtained in the medium without an inductor. The degree of destruction of bacterial and yeast biofilms achieved by the action of A. calcoaceticus IMV B-7241 surfactants obtained on refined glycerol in the presence of inductor cells was 36.5–85% and was 1.5-3 times higher compared to using surfactants synthesized in medium without inductors. Note that, surfactants synthesized in the presence of biological inductors destroyed biofilms of the test cultures at fairly low (7.5–960 μg/ml) concentrations. Similar results were observed for the usage of surfactants obtained on the waste of biodiesel production. Therefore, introduction of live cells of B. subtilis BT-2 into the medium with the crude glycerol was accompanied by synthesis of surfactants, which at concentration 1.8-960 μg/ml caused destruction of B. subtilis BT-2, Proteus vulgaris PA-12 and Enterobacter cloacae C-8 biofilms at 30.1–80.7% and was higher than using similar surfactant concentrations obtained during cultivation without inductors (24.1–75%). The destruction of biofilms of Staphylococcus aureus BMS-1, Candida albicans D-6 and Candida tropicalis PE-2 under the action of surfactants (1.8-960 μg/ml) synthesized on crude glycerol in the presence of both live or inactivated cells of B. subtilis BT-2 was 1.5–8 times higher than surfactants synthesized in medium without inductor. Conclusion. The possibility to regulate the ability to destroy bacterial and yeast biofilms of surfactants synthesized by A. calcoaceticus IMV B-7241 by introducing into the medium competitive bacteria B. subtilis BT-2 was found.
Keywords: поверхнево-активні речовини; індуктор; біоплівка; кафедра біотехнології і мікробіології; surfactants; Acinetobacter calcoaceticus ІМВ В-7241; inductor; biofilms